Analytical figures of merit: from univariate to multiway calibration - Olivieri, Alejandro Cesar (2014)
Figures of merit are numerical parameters that help to characterize the performance of a device or a system relative to alternative ones. In engineering, they are often defined for particular materials or machines in order to determine their relative utility for certain applications. In commerce, they are usually employed as marketing tools to convince consumers to choose a particular brand. Their use in analytical calibration is comparable concerning the relative success of different methodologies.